Electrolytic water oxygen catalyst, preparation method and application thereof
Patent Information
- Application Number
- CN202310480402.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-28
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-04-28
AI Technical Summary
然而,阳极析氧电极的强氧化性工作环境导致镍磷合金在析氧过程中,会发生氧化重构现象,导致其析氧催化活性稳定性不佳
[0005]有鉴于此,本发明的目的在于提供一种电解水制氧催化剂及其制备方法与应用。
Smart Images

Figure SMS_5
Abstract
Description
Technical Field
[0001] This invention belongs to the field of materials technology, specifically relating to an electrolytic water oxygen production catalyst, its preparation method, and its application. Background Technology
[0002] With the acceleration of social development, traditional non-renewable energy sources such as coal and oil are becoming increasingly depleted. In this process, environmental problems such as the greenhouse effect are becoming increasingly prominent, making the search for renewable energy sources to replace fossil fuels and other non-renewable energy sources urgent. Hydrogen energy is a new type of clean energy with low pollution and high calorific value. Hydrogen production methods mainly include water electrolysis and mineral combustion. Among these, water electrolysis has advantages such as low pollution, unrestricted application, and high purity of the produced hydrogen. However, water electrolysis consumes a large amount of electricity and has high costs, which restricts its large-scale industrial application and promotion.
[0003] Hydrogen production via water electrolysis uses water as a raw material. Through a specific electrode material-based electrocatalyst, water in the electrolyte within the electrolytic cell is decomposed into hydrogen and oxygen under the influence of electrical energy. During this process, the water in the electrolyte is oxidized into oxygen, which is then released as a gas from the electrode surface.
[0004] Nickel foam possesses a low oxygen evolution overpotential, making it a high-performance oxygen evolution catalyst. To improve the oxygen evolution catalytic activity of nickel foam, researchers have attempted to dope it with phosphorus to form a nickel-phosphorus alloy. However, the highly oxidizing working environment of the anodic oxygen evolution electrode causes oxidation and reconstruction in the nickel-phosphorus alloy during the oxygen evolution process, resulting in poor stability of its oxygen evolution catalytic activity. Summary of the Invention
[0005] In view of this, the purpose of the present invention is to provide an electrolytic water oxygen production catalyst, its preparation method and application.
[0006] In some embodiments, the present invention provides an electrolytic water oxygen production catalyst, the electrolytic water oxygen production catalyst comprising: a nickel-phosphorus alloy and a carbon layer coating the outside of the nickel-phosphorus alloy, the carbon layer comprising carbon nanomaterials.
[0007] In this application, by coating the outside of a nickel-phosphorus alloy with a carbon layer including carbon nanomaterials, the stability of the oxygen evolution catalytic activity of the water electrolysis oxygen production catalyst can be improved; at the same time, the carbon layer including carbon nanomaterials can increase the specific surface area of the water electrolysis oxygen production catalyst, thereby improving the oxygen evolution catalytic activity of the water electrolysis oxygen production catalyst.
[0008] In some embodiments of this application, the carbon layer is doped with boron and / or nitrogen.
[0009] In this application, by doping boron and / or nitrogen into the carbon layer, the oxygen evolution catalytic activity of the water electrolysis oxygen production catalyst can be further improved.
[0010] In some embodiments of this application, the nickel-phosphorus alloy is doped with iron.
[0011] In this application, by doping iron into the nickel-phosphorus alloy, the oxygen evolution catalytic activity of the water electrolysis oxygen production catalyst can be further improved.
[0012] In some embodiments of this application, this application also provides a method for preparing the electrolytic water oxygen production catalyst as described above, the preparation method comprising: S1. Preparation of phosphorus-doped nickel-based metal-organic frameworks; S2. Mix the solvent, carbon source and the phosphorus-doped nickel-based metal-organic framework obtained in step S1 to obtain a mixture, and then pyrolyze the mixture to obtain the electrolytic water oxygen production catalyst.
[0013] In some embodiments of this application, step S1, preparing a phosphorus-doped nickel-based metal-organic framework, includes: Nickel salt and dimethylimidazole were added to the solvent, stirred evenly, and then subjected to a hydrothermal reaction. After cooling and standing, the supernatant was removed, the precipitate was centrifuged and washed, and then sintered under a protective gas atmosphere. The sintered product and phosphate salt were dispersed in another solvent, stirred evenly, and then reacted. After cooling, the product was centrifuged, washed, and dried.
[0014] In some embodiments of this application, in step S1, the nickel salt includes at least one of nickel acetate, nickel sulfate, nickel nitrate, and nickel chloride.
[0015] In some embodiments of this application, in step S1, the temperature of the hydrothermal reaction is 80-120°C, preferably 90-120°C; and the time of the hydrothermal reaction is 3-5 hours, preferably 4-5 hours.
[0016] In some embodiments of this application, in step S1, the sintering temperature is 1000-1100℃, preferably 1020-1100℃; and the sintering time is 2-5h, preferably 3-5h.
[0017] In some embodiments of this application, in step S1, the solvent includes methanol, ethanol, or a mixture of both.
[0018] In some embodiments of this application, in step S1, the molar ratio of the nickel salt to dimethylimidazole is 1:2-5.
[0019] In some embodiments of this application, in step S1, the reaction temperature is 120-150°C, preferably 125-150°C; and the reaction time is 7-9 hours, preferably 7.5-9 hours.
[0020] In some embodiments of this application, in step S1, the drying temperature is 60-70°C, preferably 65-70°C; the drying time is 15-20 hours, preferably 16-20 hours.
[0021] In some embodiments of this application, in step S2, the solvent includes a hydrocarbon solvent.
[0022] In some embodiments of this application, in step S2, the carbon source includes carbon nanotubes.
[0023] In some embodiments of this application, in step S2, the mass ratio of the phosphorus-doped nickel-based metal-organic framework to the carbon source is 0.8-1.2:0.008-0.015, preferably 1-1.2:0.008-0.015.
[0024] In some embodiments of this application, in step S2, the pyrolysis temperature is 750-900℃, preferably 800-900℃; the pyrolysis time is 1-3h, preferably 2-3h.
[0025] In some embodiments of this application, in step S2, the diameter of the carbon nanotube is 1-50 nm, preferably 1-30 nm.
[0026] In some embodiments of this application, this application also provides an electrolytic water oxygen generation electrode sheet, the electrolytic water oxygen generation electrode sheet comprising a substrate and an active material layer located on the substrate, the active material layer comprising the electrolytic water oxygen generation catalyst as described above or the electrolytic water oxygen generation catalyst prepared according to the preparation method described above.
[0027] In some embodiments of this application, this application also provides an electrolytic water hydrogen production system, which includes the electrolytic water oxygen production electrode sheet as described above. Detailed Implementation
[0028] The present invention will be further illustrated by specific examples below. However, it should be noted that the specific material ratios, process conditions and results described in the embodiments of the present invention are only for illustrating the present invention and cannot be used to limit the scope of protection of the present invention. All equivalent changes or modifications made in accordance with the spirit and essence of the present invention should be covered within the scope of protection of the present invention.
[0029] This application provides a catalyst for producing oxygen through water electrolysis, which includes: a nickel-phosphorus alloy and a carbon layer coated on the outside of the nickel-phosphorus alloy, wherein the carbon layer includes carbon nanomaterials. In this application, by coating the outside of a nickel-phosphorus alloy with a carbon layer including carbon nanomaterials, the stability of the oxygen evolution catalytic activity of the water electrolysis oxygen production catalyst can be improved; at the same time, the carbon layer including carbon nanomaterials can increase the specific surface area of the water electrolysis oxygen production catalyst, thereby improving the oxygen evolution catalytic activity of the water electrolysis oxygen production catalyst. In some embodiments of this application, the carbon layer is doped with boron and / or nitrogen; In this application, by doping boron and / or nitrogen into the carbon layer, the oxygen evolution catalytic activity of the water electrolysis oxygen production catalyst can be further improved; In some embodiments of this application, the nickel-phosphorus alloy is doped with iron.
[0030] In this application, by doping iron into the nickel-phosphorus alloy, the oxygen evolution catalytic activity of the water electrolysis oxygen production catalyst can be further improved.
[0031] In some embodiments of this application, this application also provides a method for preparing the electrolytic water oxygen production catalyst as described above, the preparation method comprising: S1. Preparation of phosphorus-doped nickel-based metal-organic framework: Add nickel salt and dimethylimidazole to a solvent. The nickel salt includes at least one of nickel acetate, nickel sulfate, nickel nitrate and nickel chloride. The solvent includes methanol, ethanol or a mixture of the two. The molar ratio of nickel salt to dimethylimidazole is 1:2-5. After stirring evenly, carry out hydrothermal reaction at 80-120℃ for 3-5 hours. After cooling and standing, remove the supernatant. Centrifuge the precipitate and wash it. Then sinter it at 1000-1100℃ for 2-5 hours under a protective gas atmosphere. Disperse the sintered product and phosphorus salt in another solvent. After stirring evenly, react at 120-150℃ for 7-9 hours. After cooling, centrifuge and wash it. Then dry it at 60-70℃ for 15-20 hours. S2. Mix hydrocarbon solvent, carbon source and phosphorus-doped nickel-based metal-organic framework obtained in step S1 to obtain a mixture. The carbon source includes carbon nanotubes with a diameter of 1-50 nm. The mass ratio of phosphorus-doped nickel-based metal-organic framework to carbon source is 0.8-1.2:0.008-0.015. The catalyst for producing oxygen by electrolysis of water is obtained by pyrolyzing the mixture at 750-900℃ for 1-3 hours.
[0032] In some embodiments of this application, this application also provides an electrolytic water oxygen generation electrode sheet, which includes a substrate and an active material layer located on the substrate. The active material layer includes the electrolytic water oxygen generation catalyst as described above or the electrolytic water oxygen generation catalyst prepared according to the preparation method described above.
[0033] In some embodiments of this application, this application also provides a water electrolysis hydrogen production system, which includes the water electrolysis oxygen production electrode sheet as described above.
[0034] The present invention will be described in detail below through specific examples and embodiments. It should also be understood that the following embodiments are only for specific illustration of the present invention and should not be construed as limiting the scope of protection of the present invention. Any non-essential improvements and adjustments made by those skilled in the art based on the above description of the present invention are within the scope of protection of the present invention. The specific process parameters, etc., in the following examples are merely examples within a suitable range; that is, those skilled in the art can make appropriate selections within the appropriate range based on the description herein, and are not intended to be limited to the specific values in the examples below.
[0035] Example 1 This embodiment provides a water electrolysis oxygen production catalyst, which includes a nickel-phosphorus alloy and a carbon layer coated on the outside of the nickel-phosphorus alloy. The preparation method of the water electrolysis oxygen production catalyst is as follows: S1. Preparation of phosphorus-doped nickel-based metal-organic frameworks: Add 0.5g of nickel acetate tetrahydrate to 100ml of methanol to obtain solution A; Add 2g of 2-methylimidazole to 50ml of methanol to obtain solution B; Add all of the obtained solution A to solution B and stir well; then heat to 120°C and keep at 120°C for hydrothermal reaction for 3 hours. After cooling and standing for 15 hours, remove the supernatant, centrifuge the precipitate and wash it with methanol 3 times for 2 minutes each time. Then, under a nitrogen atmosphere and at 1100℃ for 3 hours, 5g of the sintered product and 5mg of sodium dihydrogen phosphate were ultrasonically dispersed in 30ml of water / ethanol mixed solvent (formed by deionized water and anhydrous ethanol in a volume ratio of 4:1). After stirring evenly, the mixture was reacted at 130℃ for 8.5 hours. After cooling, the mixture was centrifuged, washed, and then dried at 64℃ for 18 hours. S2. 0.01 g of carbon nanotubes with a diameter of 30 nm and 1.0 g of the phosphorus-doped nickel-based metal-organic framework prepared in step S1 were ball-milled at 1800 rpm for 5 h, and then added to 50 ml of n-hexane to obtain a mixture; The catalyst for producing oxygen by electrolysis of water was obtained by pyrolyzing the mixture at 800℃ for 2 hours.
[0036] Example 2 This embodiment provides a water electrolysis oxygen production catalyst, which includes a nickel-phosphorus alloy and a carbon layer coated on the outside of the nickel-phosphorus alloy. The preparation method of the water electrolysis oxygen production catalyst is as follows: S1. Preparation of phosphorus-doped nickel-based metal-organic frameworks: Add 0.5g of nickel acetate tetrahydrate to 100ml of ethanol to obtain solution A; Add 2.5 g of 2-methylimidazole to 60 ml of ethanol to obtain solution B; Add all of the obtained solution A to solution B and stir well; then heat to 100℃ and keep at 100℃ for hydrothermal reaction for 4 hours. After cooling and standing for 15 hours, remove the supernatant, centrifuge the precipitate and wash it with methanol 3 times for 2 minutes each time. Then, under a nitrogen atmosphere and at 1000℃ for 3.5h, 5g of the sintered product and 5mg of sodium dihydrogen phosphate were ultrasonically dispersed in 30ml of water / ethanol mixed solvent (formed by deionized water and anhydrous ethanol in a volume ratio of 4:1). After stirring evenly, the mixture was reacted at 125℃ for 8.5h. After cooling, the mixture was centrifuged, washed, and then dried at 70℃ for 15h. S2. 0.008 g of carbon nanotubes with a diameter of 25 nm and 0.8 g of the phosphorus-doped nickel-based metal-organic framework prepared in step S1 were ball-milled at 1500 rpm for 3 h, and then added to 50 ml of n-hexane to obtain a mixture; The catalyst for producing oxygen by electrolysis of water was obtained by pyrolyzing the mixture at 750℃ for 1.5 hours.
[0037] Example 3 This embodiment provides a water electrolysis oxygen production catalyst, which includes a nickel-phosphorus alloy and a carbon layer coated on the outside of the nickel-phosphorus alloy. The preparation method of the water electrolysis oxygen production catalyst is as follows: S1. Preparation of phosphorus-doped nickel-based metal-organic frameworks: Add 0.5g of nickel acetate tetrahydrate to 100ml of methanol to obtain solution A; Add 2g of 2-methylimidazole to 50ml of methanol to obtain solution B; Add all of the obtained solution A to solution B and stir well; then heat to 90°C and keep at 90°C for hydrothermal reaction for 3 hours. After cooling and standing for 15 hours, remove the supernatant, centrifuge the precipitate and wash it with methanol 3 times for 2 minutes each time. Then, under a nitrogen atmosphere and at 1050℃ for 4 hours, 5g of the sintered product and 5mg of sodium dihydrogen phosphate were ultrasonically dispersed in 30ml of water / ethanol mixed solvent (formed by deionized water and anhydrous ethanol in a volume ratio of 4:1). After stirring evenly, the mixture was reacted at 145℃ for 8 hours. After cooling, the mixture was centrifuged, washed, and then dried at 60℃ for 18 hours. S2. 0.015 g of carbon nanotubes with a diameter of 30 nm and 1.2 g of the phosphorus-doped nickel-based metal-organic framework prepared in step S1 were ball-milled at 1800 rpm for 4 h, and then added to 50 ml of n-hexane to obtain a mixture. The catalyst for producing oxygen by electrolysis of water was obtained by pyrolyzing the mixture at 780℃ for 3 hours.
[0038] Example 4 The difference between this embodiment and Embodiment 1 is that: S2. 0.01g of carbon nanotubes with a diameter of 30nm, 1.0g of the phosphorus-doped nickel-based metal-organic framework prepared in step S1, 5mg of ammonium hydrogen phosphate and 2mg of boric acid were ball-milled at 1800rpm for 5h, and then added to 50ml of n-hexane to obtain a mixture. The catalyst for producing oxygen by electrolysis of water was obtained by pyrolyzing the mixture at 800℃ for 2 hours.
[0039] Example 5 The difference between this embodiment and Embodiment 1 is that: S1. Preparation of phosphorus-doped nickel-based metal-organic frameworks: Add 0.5g of nickel acetate tetrahydrate and 0.1g of ferric nitrate nonahydrate to 100ml of methanol to obtain solution A; Add 2g of 2-methylimidazole to 50ml of methanol to obtain solution B; Add all of the obtained solution A to solution B and stir well; then heat to 120°C and keep at 120°C for hydrothermal reaction for 3 hours. After cooling and standing for 15 hours, remove the supernatant, centrifuge the precipitate and wash it with methanol 3 times for 2 minutes each time. Then, under a nitrogen atmosphere and at 1100℃ for 3 hours, 5g of the sintered product and 5mg of sodium dihydrogen phosphate were ultrasonically dispersed in 30ml of water / ethanol mixed solvent (formed by deionized water and anhydrous ethanol in a volume ratio of 4:1). After stirring evenly, the mixture was reacted at 130℃ for 8.5 hours. After cooling, the mixture was centrifuged, washed, and then dried at 64℃ for 18 hours.
[0040] Comparative Example 1 This comparative example provides a catalyst for oxygen production through water electrolysis. The preparation method of this catalyst is as follows: Add 0.5g of nickel acetate tetrahydrate to 100ml of methanol to obtain solution A; Add 2g of 2-methylimidazole to 50ml of methanol to obtain solution B; The obtained solution A and 5 mg sodium dihydrogen phosphate were ultrasonically dispersed in 30 ml of water / ethanol mixed solvent (formed by deionized water and anhydrous ethanol in a volume ratio of 4:1). After stirring evenly, the mixture was reacted at 130 °C for 8.5 h. After cooling, the mixture was centrifuged, washed, and then dried at 64 °C for 18 h. 0.01 g of carbon nanotubes with a diameter of 30 nm and 1.0 g of the phosphorus-doped nickel-based metal-organic framework prepared in step S1 were ball-milled at 1800 rpm for 5 h, and then added to 50 ml of n-hexane to obtain a mixture. The catalyst for producing oxygen by electrolysis of water was obtained by pyrolyzing the mixture at 800℃ for 2 hours.
[0041] test The oxygen evolution catalytic activity stability and oxygen evolution catalytic performance of the water electrolysis oxygen production catalysts of Examples 1-5 and Comparative Example 1 were tested. The steps for testing the stability of oxygen evolution catalyst activity are as follows: Water and anhydrous ethanol were mixed at a volume ratio of 4:1 to obtain a mixed solvent; Add 4g of water electrolysis hydrogen production catalyst and 8mL of 5.0wt% perfluorosulfonic acid polymer solution (i.e., Nafion solution) to 1L of mixed solvent, stir evenly to obtain catalyst dispersion; Five milliliters of catalyst dispersion were dropped onto the surface of a glassy carbon electrode (loading capacity approximately 0.26 mg / cm²), dried, and the catalyst-loaded glassy carbon electrode was used as the working electrode, a carbon rod as the counter electrode, and a saturated calomel electrode (SCE) as the reference electrode. Using a 1 mol / L KOH solution as the electrolyte, the oxygen evolution catalytic activity stability was tested in a three-electrode system via constant potential electrolysis (electrolysis at 150 mV overpotential for 12 h). The rate of change of current density was calculated using the following formula based on the current densities at 1 h and 11.5 h of electrolysis. The results are shown in Table 1. ; in, The rate of change of current density; and The current densities at the 1st and 11.5th hours of electrolysis are shown, both in mA / cm². 2 .
[0042] The oxygen evolution catalytic performance test steps are as follows: Water and anhydrous ethanol were mixed at a volume ratio of 4:1 to obtain a mixed solvent; Add 4g of water electrolysis hydrogen production catalyst and 8mL of 5.0wt% perfluorosulfonic acid polymer solution (i.e., Nafion solution) to 1L of mixed solvent, stir evenly to obtain catalyst dispersion; 5 ml of catalyst dispersion was dropped onto the surface of a glassy carbon electrode (loading capacity approximately 0.26 mg / cm²), dried, and used as the working electrode, a carbon rod as the counter electrode, and a saturated calomel electrode (SCE) as the reference electrode. A 1 mol / L KOH solution was used as the electrolyte. The water electrolysis oxygen production catalysts of Examples 1-5 and Comparative Example 1 were tested using linear sweep voltammetry (LSV) at 100 mA / cm². 2 The oxygen evolution overpotential at current density is shown in Table 1.
[0043] Table 1 Test Results
[0044] As shown in Table 1, compared with Comparative Example 1, the current density change rate of the water electrolysis oxygen production catalysts in Examples 1-5 is ≤5%. This indicates that the water electrolysis oxygen production catalyst of the present invention exhibits excellent stability of oxygen evolution catalytic activity.
[0045] Table 1 shows that the electrode formed by the water electrolysis oxygen production catalyst in Comparative Example 1 (without carbon layer coating) at 100 mA / cm 2 The oxygen evolution overpotential at the specified current density was 173 mV, and the rate of change at the current density was 33%. The electrode formed by the water electrolysis oxygen production catalyst in Example 1 (with carbon layer coating) at 100 mA / cm²... 2 The oxygen evolution overpotential at the specified current density was 124 mV, and the rate of change at the current density was 4%. These results indicate that the carbon coating of the nickel-phosphorus alloy in this application improved the oxygen evolution catalytic activity and stability of the water electrolysis oxygen production catalyst.
[0046] As shown in Table 1, the electrode formed by the water electrolysis oxygen production catalyst in Example 1 (without boron and nitrogen doping in the carbon layer) achieves a current of 100 mA / cm². 2 The oxygen evolution overpotential at the specified current density is 124 mV. The electrode formed by the water electrolysis oxygen production catalyst in Example 4 (with boron and nitrogen doped in the carbon layer) exhibits an overpotential of 100 mA / cm². 2 The oxygen evolution overpotential at the current density was 107 mV. This result indicates that by doping the carbon layer with boron and / or nitrogen, this application can further improve the oxygen evolution catalytic activity of the water electrolysis oxygen production catalyst.
[0047] As shown in Table 1, the electrode formed by the water electrolysis oxygen production catalyst in Example 1 (nickel-phosphorus alloy without iron doping) has an electrode strength of 100 mA / cm. 2 The oxygen evolution overpotential at the specified current density is 124 mV. The electrode formed by the water electrolysis oxygen production catalyst in Example 5 (nickel-phosphorus alloy doped with iron) exhibits an overpotential of 100 mA / cm². 2 The oxygen evolution overpotential at the current density was 103 mV. This result indicates that the present invention, by doping iron into the nickel-phosphorus alloy, can improve the oxygen evolution catalytic activity of the water electrolysis oxygen production catalyst.
[0048] The above embodiments are merely illustrative of the principles and effects of the present invention and are not intended to limit the invention. Any person skilled in the art can modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by those skilled in the art without departing from the spirit and technical concept disclosed in the present invention should still be covered by the claims of the present invention.
Claims
1. A method for preparing a catalyst for oxygen production through water electrolysis, characterized in that, The water electrolysis oxygen production catalyst comprises a nickel-phosphorus alloy and a carbon layer coating the outside of the nickel-phosphorus alloy. The preparation method includes the following steps: S1. Preparation of phosphorus-doped nickel-based metal-organic frameworks: Add 0.5g of nickel acetate tetrahydrate to 100ml of methanol to obtain solution A; Add 2g of 2-methylimidazole to 50ml of methanol to obtain solution B; Add all of the obtained solution A to solution B and stir well; then heat to 120°C and keep at 120°C for hydrothermal reaction for 3 hours. After cooling and standing for 15 hours, remove the supernatant, centrifuge the precipitate and wash it with methanol 3 times for 2 minutes each time. Then, under a nitrogen atmosphere and at 1100℃ for 3 hours, 5g of the sintered product and 5mg of sodium dihydrogen phosphate were ultrasonically dispersed in 30ml, stirred evenly, and reacted at 130℃ for 8.5 hours. After cooling, the mixture was centrifuged, washed, and then dried at 64℃ for 18 hours. The water / ethanol mixed solvent was formed by deionized water and anhydrous ethanol in a volume ratio of 4:
1. S2. 0.01 g of carbon nanotubes with a diameter of 30 nm, 1.0 g of the phosphorus-doped nickel-based metal-organic framework prepared in step S1, 5 mg of ammonium hydrogen phosphate and 2 mg of boric acid were ball-milled at 1800 rpm for 5 h, and then added to 50 ml of n-hexane to obtain a mixture. The electrolytic oxygen production catalyst is obtained by pyrolyzing the mixture at 800℃ for 2 hours; or S1. Preparation of phosphorus-doped nickel-based metal-organic frameworks: Add 0.5g of nickel acetate tetrahydrate and 0.1g of ferric nitrate nonahydrate to 100ml of methanol to obtain solution A; Add 2g of 2-methylimidazole to 50ml of methanol to obtain solution B; Add all of the obtained solution A to solution B and stir well; then heat to 120°C and keep at 120°C for hydrothermal reaction for 3 hours. After cooling and standing for 15 hours, remove the supernatant, centrifuge the precipitate and wash it with methanol 3 times for 2 minutes each time. Then, under a nitrogen atmosphere and at 1100℃ for 3 hours, 5g of the sintered product and 5mg of sodium dihydrogen phosphate were ultrasonically dispersed in 30ml of water / ethanol mixed solvent. After stirring evenly, the mixture was reacted at 130℃ for 8.5 hours. After cooling, the mixture was centrifuged and washed, and then dried at 64℃ for 18 hours. The water / ethanol mixed solvent was formed by deionized water and anhydrous ethanol in a volume ratio of 4:
1. S2. 0.01 g of carbon nanotubes with a diameter of 30 nm and 1.0 g of the phosphorus-doped nickel-based metal-organic framework prepared in step S1 were ball-milled at 1800 rpm for 5 h, and then added to 50 ml of n-hexane to obtain a mixture; The mixture was pyrolyzed at 800℃ for 2 hours to obtain the electrolytic water oxygen production catalyst.
2. An electrode plate for electrolyzing water to produce oxygen, characterized in that, The water electrolysis oxygen generation electrode sheet includes a substrate and an active material layer located on the substrate, wherein the active material layer includes an water electrolysis oxygen generation catalyst prepared according to the method described in claim 1.
3. A hydrogen production system for water electrolysis, characterized in that, The water electrolysis hydrogen production system includes the water electrolysis oxygen production electrode sheet as described in claim 2.
Citation Information
Patent Citations
Novel nickel phosphide catalyst and preparation method thereof
CN109267095A
Three-dimensional large-current oxygen evolution catalytic electrode material and preparation method and application thereof
CN115305495A